Factores de riesgo asociados a mortalidad por sepsis intraabdominal severa en pacientes postoperatorios en unidad de cuidados intensivos - Ríos Serna, Lilya Otilia (2014)
A retrospective study of cases and controls was carried out, based on the review of medical records, obtaining a sample of 240 postoperative patients with severe intra-abdominal sepsis (120 cases and 120 controls) in the Intensive Care Unit of the Regional Teaching Hospital of Trujillo during the period 2006-2012; with the aim of demonstrating whether the age, anatomical origin of the infection, comorbidity, APACHE II scale, ASA scale, serum lactate level in the first 24 hours, ventilatory support, inotropic support and number of surgical interventions are risk factors associated with mortality. The frequency of severe intra-abdominal sepsis was 31.3% and the mortality found was 60.4%. The variables that constituted risk factors associated with mortality were: age> = 65 years (OR = 3.1 and p = 0.004), APACHE scale> = 15 points (OR = 2.5 and p = 0.009), ASA scale> II (OR = 3 and p = 0.005) and lactate level> = 4 mmol / L (OR = 4.5 and p = 0.001). Regarding the anatomical origin of the infection, risk factors associated with mortality were: the pancreas (OR = 2.1 and p = 0.044), colon (OR = 1.3 and p = 0.001), cecal appendix (OR = 1.1 and p = 0.022) and hepatobiliary origin (OR = 1.7 and p = 0.041). And within the comorbidities, arterial hypertension (OR = 1.2 and p = 0.002), chronic obstructive pulmonary disease COPD (OR = 1.6 and p = 0.009) and heart failure (OR = 1.4 and p = 0.035) were risk factors. Using a logistic regression model, it was shown that the variable APACHE scale was the one that had more association with mortality (OR = 18.30 and p <0.00000). In conclusion, age, APACHE scale, ASA scale and lactate level were identified as risk factors associated with mortality; being the APACHE scale the one that determined a greater risk of mortality. And within the anatomical origin of infection and comorbidities, the colon and arterial hypertension respectively had more association with mortality